Correlation between Galectin-3 and Adverse Outcomes in Myocardial Infarction Patients: A Meta-Analysis - Lei Tian; Kan Chen; Zhihua Han (Cardiology Research and Practice)
Background. Acute myocardial infarction (AMI) is a disease with high morbidity and mortality. Some new biomarkers can help us to improve the life quality and prognosis of AMI patients. Objective. We therefore performed a systematic review and meta-analysis on the use of galectin-3 (gal3) for assessing prognosis of AMI patients. Methods. We searched Medline, Embase, Web of Science, Cochrane Library, SinoMed, China National Knowledge Infrastructure (CNKI), and Wanfang database up to June 2019. Trials included using galectin-3 to estimate prognosis in myocardial infarction (MI) patients. Results. We identified 10 trails with a total of 2809 participants. The negative correlation between galectin-3 and left ventricular ejection fraction (LVEF) was significant in 505 AMI patients (Fisher's Z −0.22, 95% CI: −0.34, −0.09). The correlation between galectin-3 and infarct size was not significant in 119 patients (Fisher's Z 0.12, 95% CI: −0.36, 0.60). Higher galectin-3 was associated with increased all-cause mortality in 2343 AMI patients (Fisher's Z 1.58, 95% CI: 1.23, 2.03). Conclusion. The limited evidence suggests that galectin-3 is likely to predict the adverse outcomes in MI patients, but it is not significantly correlated with infarct size after MI. More high-quality trials with longer-term follow-up are still needed to confirm this finding.